PENERAPAN INOVASI INKREMENTAL SEBAGAI STRATEGI BERKELANJUTAN DI HOTEL GRAND MERCURE MEDAN ANGKASA: PERSPEKTIF TRIPLE BOTTOM LINE - Ngatemin; Suwandi, Rachmad; Emrizal (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2025)
This research takes the topic of inkremetal innovation implementation as a sustainable strategy at Grand Mercure Medan Angkasa Hotel from the triple bottom line perspective. The purpose of this research is to evaluate the application of the concept of sustainability at the Grand Mercure Medan Angkasa Hotel at this time from the triple bottom line perspective, mapping guests at the Grand Mercure Medan Angkasa Hotel assessed based on “sustainability concern” and “sustainability practice” and designing inkremetal innovation as a sustainable strategy at the Grand Mercure Medan Angkasa Hotel using the action priority matrix model. This type of research is action research using quantitative and qualitative approaches. Data collection is done by survey, interview, observation and documentation. Data analysis using quadrant analysis and descriptive statistics. The findings of this study are (1) Evaluation of the application of the triple bottom line at the Grand Mercure Medan Hotel at this time in terms of effectiveness, efficiency, equity, responsiveness, adequacy, and accuracy is required guest engagement in the hotel sustainability program. (2) The description of the guests of the Grand Mercure Medan Angkasa hotel studied based on sustainability concern and sustainability practice is a high sustainability concern guest, low sustainability practice as much as 12.60%, high sustainability concern guest, high sustainability practice as much as 20.47%, low sustainability concern guest, low sustainability practice 38.58%, low sustainability concern guest, high sustainability practice as much as 28.35%. Inkremetal innovations of Grand Mercure Medan Angkasa Hotel in engaging guests in sustainable practices are using automatic taps, guest-based initiatives, providing visual cues, providing brief and interesting information about sustainability at various guest contact points such as elevators, bathrooms, and restaurants. The implication of the research is a variety of innovations to improve sustainability at Grand Mercure Medan Angkasa Hotel